Work Motivation and Organizational Commitment in the Sustainability of Culinary SMEs - Elizabeth, Roosganda; Notosudjono, Didik; Hamzah, Hamzah (Research Horizon, 2025)
This study examines the important role of work motivation and organizational commitment in supporting the sustainability of culinary Small and Medium Enterprises (SMEs). Using a qualitative approach, data were collected through in-depth interviews, participant observation, and document analysis involving SME owners and employees. The results of this study revealed that intrinsic and extrinsic motivation significantly influence employee commitment to the organization, which is essential for long-term business resilience and success. Intrinsic motivations such as personal passion for culinary work, a sense of purpose, and a desire to create encourage employees to remain dedicated and proactive in their roles. On the other hand, extrinsic motivators such as financial incentives, career advancement opportunities, and recognition for achievements further enhance their drive and job satisfaction. The study found that high levels of organizational commitment, especially when shared by owners and staff, contribute to SMEs’ ​​ability to survive amidst market volatility and intense competition. To foster such commitment, this study recommends that business owners create a supportive work culture by investing in employee training, ensuring open communication, and recognizing performance.